Phycobilisome Diffusion Is Required for Light-State Transitions in Cyanobacteria - Joshua, Sarah (American Society of Plant Biologists, 2004)
Phycobilisomes are the major accessory light-harvesting complexes of cyanobacteria and red algae. Studies using fluorescence recovery after photobleaching on cyanobacteria in vivo have shown that the phycobilisomes are mobile complexes that rapidly diffuse on the thylakoid membrane surface. By contrast, the PSII core complexes are completely immobile. This indicates that the association of phycobilisomes with reaction centers must be transient and unstable. Here, we show that when cells of the cyanobacterium Synechococcus sp. PCC7942 are immersed in buffers of high osmotic strength, the diffusion coefficient for the phycobilisomes is greatly decreased. This suggests that the interaction between phycobilisomes and reaction centers becomes much less transient under these conditions. We discuss the possible reasons for this. State transitions are a rapid physiological adaptation mechanism that regulates the way in which absorbed light energy is distributed between PSI and PSII. Immersing cells in high osmotic strength buffers inhibits state transitions by locking cells into whichever state they were in prior to addition of the buffer. The effect on state transitions is induced at the same buffer concentrations as the effect on phycobilisome diffusion. This implies that phycobilisome diffusion is required for state transitions. The main physiological role for phycobilisome mobility may be to allow such flexibility in light harvesting.